2021
DOI: 10.1002/oby.23331
|View full text |Cite
|
Sign up to set email alerts
|

SGLT inhibitors on weight and body mass: A meta‐analysis of 116 randomized‐controlled trials

Abstract: Objective Multiple trials have demonstrated the metabolic effects of sodium/glucose cotransporter 2 (SGLT2) inhibitors in patients regardless of diabetes status, and recent trials have been conducted on the combined sodium/glucose cotransporter 1 and sodium/glucose cotransporter 2 (SGLT1/SGLT2) inhibitors. Therefore, a meta‐analysis was conducted to investigate the weight reduction effects and dose‐response relationship of SGLT inhibitors and to assess the relative efficacy of SGLT1/SGLT2 inhibitors. Methods F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 44 publications
(46 reference statements)
0
18
0
Order By: Relevance
“…The glucosuric effect of SGLT2-i is associated with weight loss ( Figure 2 ). In a recent meta-analysis, treatment with SGLT2-i, compared with placebo, generated a significant mean weight reduction of −1.79 kg (95% CI: −1.93; −1.66, p < 0.001) [ 94 ]. In patients with HF, SGLT2-i reduced body weight by −1.36 kg; (95% CI: −1.68; −1.03; p < 0.001) [ 83 ].…”
Section: Current Antidiabetic Drugs and The Influence Of Hypertensionmentioning
confidence: 99%
“…The glucosuric effect of SGLT2-i is associated with weight loss ( Figure 2 ). In a recent meta-analysis, treatment with SGLT2-i, compared with placebo, generated a significant mean weight reduction of −1.79 kg (95% CI: −1.93; −1.66, p < 0.001) [ 94 ]. In patients with HF, SGLT2-i reduced body weight by −1.36 kg; (95% CI: −1.68; −1.03; p < 0.001) [ 83 ].…”
Section: Current Antidiabetic Drugs and The Influence Of Hypertensionmentioning
confidence: 99%
“…While there is an increase in the relative risk of adverse reactions (mycotic genital infection, UTI, and lower limb amputation), the absolute benefit currently outweighs the risk. Several meta-analyses involving the above trials have demonstrated a positive weight loss outcome with SGLT2i compared to placebo [ 48 , 49 ]. However, to date, there are no published trials of SGLT2i specifically in patients with obesity.…”
Section: Randomized Controlled Trials On Sodium-glucose Cotransporter...mentioning
confidence: 99%
“…Using these parameters, we will have 90% power to detect statistically signi cant differences between the groups at α 0.05. This estimation was based on the available evidence for body weight reduction using Liraglutide 3mg daily (13) or Semaglutide 1mg weekly (14) , Dapagli ozin 10mg daily (15) and the weight loss achieved at the DDI when standard care is provided in people with T1D.…”
Section: Sample Size {14}mentioning
confidence: 99%